PREVALENCE OF SARCOPENIA AND SARCOPENIC OBESITY AMONG COMMUNITY-DWELLING OLDER ADULTS: A CROSS-SECTIONAL PILOT STUDY - Ali Mir, Imtiyaz; Jia Qi Phang; Mohammed Abdulrazzaq Jabbar; Syeda Humayra (Malaysian Journal of Public Health Medicine, 2024)
Sarcopenic obesity (SO) is characterized by age-related decline in muscle mass and function with increased body fat. SO is associated with higher risk of physical disability, hospitalization, metabolic syndrome, cardiovascular disorders and mortality. To date, no study has been carried out on prevalence of SO in community-dwelling older adults in Malaysia. Objective of this study was to determine the prevalence of sarcopenia and SO among community-dwelling older adults. Using the convenient sampling technique, a total of 65 participants of both genders aged 60 years and above were recruited. Physical performance, muscle strength and muscle mass, and body fat percentage were measured by gait speed, handgrip strength, and bioelectrical impedance analysis respectively. European Working Group on Sarcopenia in Older People 2 diagnostic algorithm was used to determine the SO, based on the cut-off points from American Society of Bariatric Physicians and Asian Working Group for Sarcopenia. Out of 65 participants, 27 were males (41.5%) and 38 were females (58.5%). Overall prevalence of sarcopenia was 7.7% (n=5) and this was reported only in female (13.2%) participants. Similarly, SO was only prevalent in females (5.3%), with overall prevalence of 3.1%. Age and gender were significantly associated with sarcopenia (p=0.000; p=0.005 respectively), but SO showed no such association with gender (p=0.226) or age (p=0.814). Prevalence of sarcopenia and SO is relatively lower among Malaysian Chinese community-dwellers. The prevalence of sarcopenia and SO was only exhibited by the female population. Future studies with a larger sample should be conducted to address the paucity of current literature regarding SO in the Asian population.